Yusif Sayigh Arab economist and Palestinian patriot́ : a fractured life story - Ṣāyiġ, Yūsuf ʿAbdallāh 1916-2004 (New York, 2015)
An acclaimed economist and lifelong Palestinian nationalist Yusif Sayigh (1916-2004) came of age at a time of immense political change in the Middle East. Born in al-Bassa, near Acre in northern Palestine, he was witness to the events that led to the loss of Palestine and his memoir therefore constitutes a vivid social history of the region, as well as a revealing firsthand account of the Palestinian national movement almost from its earliest inception. Family and everyday life, co-villagers, landscapes, pleasures, outings, schooling, and political figures recreate the vanished world of Sayigh's formative years in the Levant. An activist in Palestine, he was taken prisoner of war by the Israelis in 1948. Later, as an economist, he wrote extensively on Arab oil, economic development, and manpower, teaching for many years at the American University of Beirut and taking early retirement in 1974 to work as a consultant for a number of pan-Arab and international organizations. A single chapter on Palestinian politics provides insights into his later activist work and experiences of working as a consultant with the Palestine Liberation Organization to produce an economic plan for an eventual Palestinian state.This fascinating memoir by a pioneer and major figure of the Palestinian national movement is a welcome addition to the growing literature on Palestinian life during the first half of the twentieth century as well as an account of some of the most pressing political and economic issues to have faced the Arab world for the better part of the twentieth century -- Book jacket
Based on the oral memoirs of Yusif Sayigh. - Includes "List of Yusif Sayigh's publications" (pages 365-375)
Keywords: Ṣāʼigh, Yūsuf ʻAbd Allāh / 1916-2004 / Biography; Ṣāyiġ, Yūsuf ʻAbdallāh / 1916-2004; Ṣāyiġ, Yūsuf ʿAbdallāh -- 1916-2004; Economists / Palestine / Biography; Wirtschaftswissenschaftler; Volkswirtschaft; 1.1\x / Ökonomen; 1.2\x / Palästina; Arabische Staaten; Palästina; Biografie